Association between platelet to lymphocyte ratio and saphenous vein graft disease in patients with stable angina pectoris - Kundi, Harun (Anatol J Cardiol, 2016)
OBJECTIVE: In this study, we aimed to investigate the relation of platelet to lymphocyte ratio (PLR) in saphenous vein graft disease (SVGD) in patients with stable angina pectoris after coronary artery bypass graft surgery. METHODS: A total of 455 patients were included in the study. There were 210 patients with SVGD and 245 patients without SVGD. The effects of different variables on SVGD were computed in logistic regression analysis. RESULTS: The platelet count, lymphocyte count, PLR, high-density lipoprotein (HDL), Na, and ALT were significantly associated with SVGD. In multivariate regression analysis, HDL and PLR were found to be significantly associated with SVGD. CONCLUSION: To the best of our knowledge, this is the first study showing the significant association of PLR with SVGD. This study suggests that PLR can be used as a marker of SVGD because it is an easily available and inexpensive test.